Safe behavior and sociodemographic factors among the workers in an aircraft manufacturing company - Haikal, Shafari; Nor Aslina, Abd Jalil; Mohammad Adam, Adman (AIP Publishing, 2023)
Workers in the aircraft manufacturing industry are exposed to a higher risk of increasing accidents due to unsafe behavior at the workplace. This paper aims to assess whether safe behavior differed based on the sociodemographic factors among the workers. A total of 48 respondents participated in a survey conducted at an aircraft manufacturing company in the Klang Valley, Malaysia. The study highlights that majority of the respondents had tertiary qualifications (62.5%) and have been working at the company for more than three years (68.1%). There are significant differences in safe behavior based on gender, ethnicity, education level, marital status, number of dependents, job nature, and job role. This study also found that most respondents agree that safety at their workplace is appropriately in place. Our result suggests that the employer endure continual safety training for all workers. Therefore, the education and working experience of the workers may raise safe behavior at the workplace. Good safety management in an organization is also essential to motivate workers to work safely.